2004
DOI: 10.1128/jcm.42.6.2759-2765.2004
|View full text |Cite
|
Sign up to set email alerts
|

Use of a Recombinant Envelope Protein Subunit Antigen for Specific Serological Diagnosis of West Nile Virus Infection

Abstract: Serological diagnosis of West Nile virus (WNV) infection is complicated by extensive antigenic crossreactivity with other closely related flaviviruses, such as St. Louis encephalitis virus.Here we describe a recombinant, bacterially expressed antigen equivalent to structural domain III of the WNV envelope protein that has allowed clear discrimination of antibody responses to WNV from those against other related flaviviruses in indirect enzyme-linked immunosorbent assays using standardized control antisera and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
40
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 59 publications
(42 citation statements)
references
References 22 publications
2
40
0
Order By: Relevance
“…Strategies to differentiate current flavivirus infections have been proposed, such as by determining the IgMto-IgG ratio (15,36), by using recombinant EDIII or nonstructural protein 1 (NS1) as an antigen (2,36), or by epitopeblocking ELISA (12,19). All of these assays have limitations, including requiring the simultaneous testing of serum specimens for IgM and IgG, requiring paired acute-and convalescent-phase serum specimens, or the observation that not all infected individuals develop antibody against EDIII or NS1 antigen.…”
Section: Discussionmentioning
confidence: 99%
“…Strategies to differentiate current flavivirus infections have been proposed, such as by determining the IgMto-IgG ratio (15,36), by using recombinant EDIII or nonstructural protein 1 (NS1) as an antigen (2,36), or by epitopeblocking ELISA (12,19). All of these assays have limitations, including requiring the simultaneous testing of serum specimens for IgM and IgG, requiring paired acute-and convalescent-phase serum specimens, or the observation that not all infected individuals develop antibody against EDIII or NS1 antigen.…”
Section: Discussionmentioning
confidence: 99%
“…There are several examples of the use of recombinant E proteins of WNV to develop diagnostic tests that are based on the indirect ELISA format (3,13,21,35). However, in a preliminary study using a competitive ELISA format, we found that WNV serum-neutralizing antibodies in most equine sera did not inhibit 5E8 binding to recombinant E protein expressed in Escherichia coli, perhaps due to conformational alterations in critical antigenic structures in the recombinant E protein.…”
Section: Discussionmentioning
confidence: 91%
“…Furthermore, the PRNT is not suitable for large-scale screening of susceptible animals, i.e., for monitoring population (or herd) immunity or measuring vaccine efficacy and infection. Recently, several enzyme-linked immunosorbent assays (ELISAs) have been developed and used in serologic testing for WNV infection, mainly in humans and horses (3,5,35). Although these ELISAs have been useful in detecting exposed individuals, test results do not directly correlate with the development of protective immunity against WNV in those individuals.…”
mentioning
confidence: 99%
“…MIAFs raised against WNV lineage I, WNV lineage II, Japanese encephalitis virus (JEV) Nakayama, St. Louis encephalitis virus (SLEV) Parton, and Bagaza virus (BAGV) DakAr B209 were acquired from the WRCEVA collection. Previously described human sera from WNV-infected patients were also used (63). The deidentified sera were used under an exemption approved by the UTMB Institutional Review Board.…”
Section: Methodsmentioning
confidence: 99%